The choice of intense sweetener in the composition of medicated chewing gum under development - Yu. S. Maslii; O. A. Ruban; І. V. Kovalevska (The State Expert Center of the Ministry of Health of Ukraine, 2019)
Considering the simplicity and ease of use, in recent years, more and more attention deserves medicated chewing gum (MCG), which plays the role of oral drug delivery system. Since this product remains in the oral cavity for a longer time than other oral medicines, the taste is one of the important features of the MCG. It is known, that one of the ways to correct and mask the taste of medicines is the addition of intense sweeteners, which not only affect the taste characteristics of the ready product, but also can influence the physic-chemical and technological properties of the active components. The aim of this work was the selection of the optimal intensive sweetener in the developed dental MCG with lysozyme hydrochloride and ascorbic acid. As natural flavourers, we studied natural and synthetic intensive sweeteners: potassium acesulfame, aspartame, sodium cyclamate, sodium saccharin, stevia and sucralose. The choice of flavouring agents was carried out using organoleptic methods for evaluating the taste with the help of numerical indexes by A. I. Tentsova and use of alphabetic and numerical indexes by I. A. Yegorov, and also by studying the crystallographic properties of intense sweeteners and their mixtures with active pharmaceutical ingredients. According to the obtained results, all compositions, except for the sample with sodium saccharin, had a corrective property and had a similar sweet-sour taste. However, not all of them had a long sweet aftertaste, which is very important for this dosage form. The highest numerical indices were samples of MCG with sodium cyclamate, stevia and sucralose. By conducting a microscopic analysis of mixtures of active pharmaceutical ingredients with the investigated intense sweeteners were predicted possible methods of obtaining the developed solid dosage form - the method of direct compression or the use of preliminary granulation. Taking into account the complex of the obtained results, sucralose has the best correcting and physic-chemical characteristics of all the investigated intense sweeteners.